The Correlation between the Internationalization Processes and Performance of Firms: The Case of Emerging Market Firms of the BRIC Countries - Aysun Ficici; Lingling Wang; C. Bulent Aybar; Bo Fan (Journal of Economics and Political Economy, 2014)
In this empirical study we examine the correlation between the internationalization processes and financial performance of firms by focusing on the emerging market firms (EMNCs) that originate from the BRIC countries. We test the shape of the internationalization - performance curve and explore the differences on effectiveness of the sectors. Our sample data that is collected from the World Scope database that includes a total of 239 firms in which 13 of the firms are from Brazil, 58 of them from China, 156 from India, and 12 from Russia. The internationalization activities take place during the period of 2000 – 2010. Our results suggest that using only the first order term FSTS and second order term FSTS², demonstrates a positive relationship between DOI and ROA, a negative relationship between DOI and ROE, and DOI and ROS, and a positive relationship between DOI and ROA, DOI and ROS, and a negative relationship between DOI and ROE. The sign of the coefficient for FSTS are negative and for FSTS², positive. This result confirms the previous theories that financial performance decreases in the beginning of the internationalization processes, then increases with the expansion of international operations. These results are statistically significant and propose a U-shaped relationship between the financial performance of EMNCs and their degree of internationalization.
Keywords: F2; F21; F23; 330; Emerging Markets; Emerging Market Multinationals; Financial Performance; Foreign Direct Investment